Discovery of a Pseudobulge Galaxy Launching Powerful Relativistic Jets - Jari K. Kotilainen; Jonathan León-Tavares; Alejandro Olguín-Iglesias; Maarten Baes; Christopher Anórve; Vahram Chavushyan; Luis Carrasco (IOP Science, 2022)
Supermassive black holes launching plasma jets at close to the speed of light, producing gamma-rays, have ubiquitously been found to be hosted by massive elliptical galaxies. Since elliptical galaxies are generally believed to be built through galaxy mergers, active galactic nuclei (AGN) launching relativistic jets are associated with the latest stages of galaxy evolution. We have discovered a pseudobulge morphology in the host galaxy of the gamma-ray AGN PKS 2004-447. This is the first gamma-ray emitter radio-loud AGN found to have been launched from a system where both the black hole and host galaxy have been actively growing via secular processes. This is evidence of an alternative black hole-galaxy co-evolutionary path to develop powerful relativistic jets, which is not merger driven.